(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Plamoottil M. 2021. Heteropneustes fuscus (Siluriformes: Heteropneustidae), a new catfish species from Kerala, India. Biodiversitas 22: 87-98. Heteropneustes fuscus, a new catfish species, is described from Kerala, India; it is a close congener of Heteropneustes fossilis (Bloch, 1794) described from Tranquebar in Tamil Nadu. Heteropneustes fuscus has been misidentified as H. fossilis until now, but it differs from Bloch’s species in color and many other rigid taxonomic variables. The new species can be distinguished from its relative species in the following combination of characters: deep black body and fins, 4-5 branched dorsal-fin soft rays, 72-75 anal fin rays, 58-60 total vertebrae, 26-32 total gill rakers; deeper and wider body; deeper caudal peduncle; greater pre occipital and post occipital distances and longer anal fin. The new fish is edible and found in freshwater rivers, streams, ponds and paddy fields in Kerala. It is also cultivated in some artificial impoundments. Heteropneustes fuscus is compared with its congeners, scientifically named and taxonomically described.